A bio-syringe mechanism and the pattern of genital correspondence in the weevil genus Sitona (Coleoptera: Curculionidae): an approach to the great interest of Sharp and Muir - Alichi, Mahmood (Zootaxa, 2021)
The remarkable diversity in male and female genital morphology among the species of Sitona Germar might contribute to the understanding of the structural “lock-and-key” isolating mechanism. Recently, it has been found that in spite of the phallic sizes in male weevils of the genus Sitona, their internal sacs should precisely match with the vaginal infoldings of conspecific females. The present research also deals with the male transfer apparatus, which is a special organ for insemination procedure inside the female bursa copulatrix. A wedge-shaped structure with a fused ejaculatory pump was distinguished as the bio-syringe part of the transfer apparatus in the examined species. Two paired sclerites of the transfer apparatus support the bio-syringe, so that it would slide freely between them and lock precisely over the opening of the spermathecal duct inside the bursa copulatrix of the female. In this phenomenon, several new structures were also found, including a bursal sclerite (“bursal disc”) and a pair of miniature pouches (“bursal plugs”) which are embedded in the thickened wall of the female bursal lumen. These findings explain how the shapes of male and female copulatory organs are normally species-specific and provide an opportunity for understanding the role of the structural lock-and-key isolating mechanism.